CHEMICAL COMPOSITION OF ESSENTIAL OILS FROM LEAVES AND SEEDS AND ARYLS OF KALAK PACUNG(Horsfieldia subglobosa) (Myristicaceae) - Praptiwi, - - (LIPI Press, 2015)
ABSTRACT The aim of the study was to determine the chemical composition of the essential oil of kalak pacung (Horsfieldia subglobosa) from different part of the plant (leaves and seeds and aryl). The essential oil was obtained by hydro-distillation, while its chemical compounds were separated and identified by gas chromarography-mass spectrometry (GS-MS). GC-MS analysis of the seed and aryl oil showed that it consisted of 58 compounds, 50 compounds of which were identified, representing 86,56% of the whole. Meanwhile, the leaf essential oil consisted of 75 compounds, with 61 compounds identified represented 98,35%. The main compounds of seed and aryl essential oil were (-) spathulenol type 2 (9.45%), naphtalene type 1 (7.40%) and type 2 (7.40%). The compounds of leaf oil with concentration more than 5% were isocaryophyllene (13.29%), a-Copaene (6.62%), and naphthalene (6.88%).